Applications and challenges of immunotherapy in the management of gastric adenocarcinoma: current status and future perspectives - Zhiyao Chen; Yunbin Ma; Jianan Chen (World Journal of Surgical Oncology)
Abstract Gastric adenocarcinoma (GAC) remains a significant global public health challenge, characterized by high incidence and mortality rates. Progress in tumor immunology has introduced immune checkpoint inhibitors (ICIs) targeting the programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) pathways, demonstrating substantial potential in GAC therapy. Clinical research indicates that ICIs, particularly when combined with chemotherapy or targeted therapies, significantly enhance treatment efficacy in advanced GAC and specific molecular subtypes, including microsatellite instability-high (MSI-H) and human epidermal growth factor receptor 2 (HER2)-positive patients. However, immunotherapy is also associated with a range of immune-related adverse events (irAEs), necessitating effective management strategies to ensure treatment safety and maintain patients’ quality of life. Future studies should focus on identifying new therapeutic targets, optimizing patient selection, and developing personalized treatment approaches to further improve the efficacy and safety of immunotherapy in GAC.